Liberalization of retail sector and the economic impact of the entry of foreign hypermarkets on local retailers in Klang Valley, Malaysia - Kalliappan, S. R.; Alavi, Rokiah; Abdullah, Kalthom; Zakaullah, Muhammad Arif (Faculty of Economics and Management, Universiti Putra Malaysia, 2008)
The primary purpose of this research is to investigate the impact of liberalization of retail sector via the presence of foreign hypermarkets in Malaysia on local retailers. Both quantitative and qualitative methods (survey and interviews) were used to collect and analyze the data. A total of 135 questionnaires were completed. The findings from the survey reveal that the entry of foreign hypermarkets in a town often affects the business environment of the local retail businesses. It is found that the newly established foreign hypermarkets tend to acquire much larger market share from the existing local businesses. The survey found that some businesses benefited from the presence of foreign hypermarkets (especially complementary type of retail businesses) while others do not (specifically those retail businesses that are related to groceries).